2014
DOI: 10.3945/ajcn.114.083832
|View full text |Cite
|
Sign up to set email alerts
|

The double burden of undernutrition and excess body weight in Mexico

Abstract: Background: In Mexico, stunting and anemia have declined but are still high in some regions and subpopulations, whereas overweight and obesity have increased at alarming rates in all age and socioeconomic groups. Objective: The objective was to describe the coexistence of stunting, anemia, and overweight and obesity at the national, household, and individual levels. Design: We estimated national prevalences of and trends for stunting, anemia, and overweight and obesity in children aged ,5 y and in school-aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
93
0
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(116 citation statements)
references
References 21 publications
13
93
0
10
Order By: Relevance
“…As mentioned previously, Mexico is undergoing a nutrition transition characterized by declining rates of undernutrition in past decades and increasing rates of obesity in all age groups. It has been suggested that Mexico may be experiencing an advanced stage of the nutrition transition due to lower than expected prevalences of the coexistence of the conditions at the household and individual levels, particularly overweight/ obesity with anemia and stunting in school-aged children [3]. Yet, the presence of the double burden at national, household and individual levels is an onorous public health concern and comprises a complex interplay of social, economic and political factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned previously, Mexico is undergoing a nutrition transition characterized by declining rates of undernutrition in past decades and increasing rates of obesity in all age groups. It has been suggested that Mexico may be experiencing an advanced stage of the nutrition transition due to lower than expected prevalences of the coexistence of the conditions at the household and individual levels, particularly overweight/ obesity with anemia and stunting in school-aged children [3]. Yet, the presence of the double burden at national, household and individual levels is an onorous public health concern and comprises a complex interplay of social, economic and political factors.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas most public policies have focused on prevention of undernutrition, these efforts addressing excessive consumption of sugar-sweetened beverages target the widespread prevalence of obesity in Mexico, which is now recognized as an epidemic [1]. However, a substantive prevalence of undernutrition (stunting, anemia) still exists in some regions and population groups in Mexico, despite the decline in undernutrition in the past few decades [3]. Thus, it is essential to assess early childhood feeding practices within the context of the double burden of undernutrition and obesity facing the Mexican population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A brief overview of the studies' characteristics is presented in Table 2, and some important features are described in the following sections. Eight articles provided a general review [ [35][36][37][38][39][40][41][42], and 2 examined the DBMN situation in Africa [43,44].…”
Section: Published Studies Examining Dbmn In Developing Countriesmentioning
confidence: 99%
“…In particular, lead exposure remains a public health problem for childbearing women, their developing fetuses and may have lifelong impacts on children’s growth and development. Mexico is unique in that both stunting and obesity are major public health concerns in children (Kroker-Lobos et al 2014). There are many risk factors for lead exposure, the most common of which are use of traditional lead glazed pottery (the main exposure factor for the general population), pica (the eating of nonfood substances), occupational exposure (directly or indirectly from the inadvertent transfer of lead dust from the workplace on workers’ clothing, shoes or bodies), use of alternative remedies or cosmetics, air pollutants and nutritional sources (due to food wrappers and water sources) (Bakhireva et al 2013; Brown et al 2000; Meneses-Gonzalez et al 2003; Romieu et al 1994; CDC 2010).…”
Section: Introductionmentioning
confidence: 99%